Gender differences in itch and pain-related sensations provoked by histamine, cowhage and capsaicin - Hartmann, Elisabeth; Handwerker, Hermann Otto; Forster, Clemens (Acta Dermato-Venereologica, 2015)
Cowhage, capsaicin and histamine, all applied via spicules, were used to induce itch and pain-related sensations in 15 male and 15 female subjects. Sensory qualities were assessed by questionnaire; intensities and time courses of the "itching" and "burning" sensation were measured alternately, but continuously on a VAS. In addition, axon reflexes were assessed. Only histamine and capsaicin produced a clear axon reflex flare (histamine > capsaicin, male = female). The 3 types of spicules caused mixed burning and itching sensations with different time courses. In the beginning burning prevailed, in the following minutes histamine induced mostly itching, capsaicin predominantly burning, cowhage both sensory components equally. Female subjects experienced more pain-related sensations (questionnaire), and their ratings leaned more toward burning than those of males. These findings indicate that the mixed itching and burning sensations are differentially processed by both genders. No indications were found for gender specific differential processing in the primary afferents as reflected by nearly identical flare responses.
EVALuna2:2482